Outcomes of renal transplantation in patients with AL amyloidosis: an international collaboration through The International Kidney and Monoclonal Gammopathy Research Group - Havasi, Andrea; Heybeli, Cihan; Leung, Nelson; Angel-Korman, Avital; Sanchorawala, Vaishali; Cohen, Oliver; Wechalekar, Ashutosh; Bridoux, Frank; Jaffer, Insara; Gutgarts, Victoria; Hassoun, Hani; Levinson, Maya; et al. (Blood cancer journal, 2022)
Effective systemic therapies suppress toxic light chain production leading to an increased proportion of patients with light chain (AL) amyloidosis who survive longer albeit with end-stage renal disease. There is a critical need to identify patients in this population who benefit from renal transplantation. This multicenter, observational study from five countries includes 237 patients with AL amyloidosis who underwent renal transplantation between 1987 and 2020. With a median follow-up of 8.5 years, the median overall survival from renal transplantation was 8.6 years and was significantly longer in patients with complete and very good partial hematologic responses (CR + VGPR) compared to less than VGPR (9 versus 6.8 years; HR: 1.5, P = 0.04 [95% CI: 1-2.1]) at renal transplantation. Median graft survival was 7.8 years and was better in the CR + VGPR group (8.3 vs 5.7 years, HR: 1.4, P = 0.05 [95% CI: 1-2]). The frequency and time to amyloid recurrence in the graft was also lower (16% vs 37%, p = 0.01) and longer (median time not achieved vs 10 years, p = 0.001) in the CR + VGPR group. Comparing CR vs. VGPR there was no difference in overall or graft survival. Although 69 patients (29%) experienced hematologic relapse, treatment effectively prevented graft loss in the majority (87%). Renal transplantation in selected AL amyloidosis patients is associated with extended overall and renal graft survival. Patients with hematologic CR or VGPR have the most favorable outcomes, and these patients should be considered for renal transplantation.